The relationship between neutrophil to lymphocyte ratio (NLR) with rehospitalisation and mortality in patients with acute coronary syndrome (ACS) - Jesse Lesmana; Achmad Lefi (Journal of the Pakistan Medical Association, 2024)
Objective: To determine the relationship of neutrophil-to-lymphocyte ratio with re-hospitalisation rate and death in acute coronary syndrome patients. Methods: The retrospective, observational, analytical study was conducted at Surabaya Hospital, East Java, Indonesia, and comprised data of acute coronary syndrome patients from January to December 2021. Neutrophilto- lymphocyte ratio values taken during each admission were noted, and divided into 3 groups; <3, 3-5 moderate, and >5 high. Data was also noted for the frequency of rehospitalisation and mortality from the institutional medical records. Data was analysed using SPSS 23. Results: Of the 102 patients, 83(81.4%) were males and 19(18.6%) were females. The overall mean age was 56.78±11.53 years. There were 48(47%) patients with low neutrophil-to-lymphocyte ratio, and 27(26.5%) each in the moderate and high categories. There was a strong relationship between neutrophil-to-lymphocyte ratio and mortality (p=0.038). The relationship between neutrophil-to-lymphocyte ratio and rehospitalisation was not significant (p=0.264). Conclusion: The neutrophil-to-lymphocyte ratio was associated with mortality during treatment, but was not associated with the incidence of rehospitalisation in acute coronary syndrome patients. Key Words: Incidence, Prognosis, Coronary, Mortality, Rehospitalisation.